2015
DOI: 10.1002/hed.23972
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transnasal approaches to pterygopalatine fossa tumors

Abstract: The endoscopic transnasal approaches are safe and feasible techniques for the radical resection of selected tumors involving the PPF and should be tailored according to the biology and extension of the lesion. © 2015 Wiley Periodicals, Inc. Head Neck 38: E214-E220, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 16 publications
(41 reference statements)
1
40
0
2
Order By: Relevance
“…1,2 Management of penetrating trauma to the paranasal sinuses and skull base with retained foreign bodies represents a challenge due to the proximity to vital neurovascular structures. 3,4 Preoperative CT scan is the preferred modality to show bony landmarks and vascular structures; however, although both CT scan and magnetic resonance imaging are increasingly being used, in the case of nail gun injuries significant artefacts secondary to the nail probably preclude these studies. 5 Blind removal of foreign bodies has been reported, 6 however the development of combined-multiportal endoscopic approaches enabled surgeons to reach different regions through minimally invasive routes with lower incidence of complications, lower morbidity, and mortality rates compared with traditional external approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Management of penetrating trauma to the paranasal sinuses and skull base with retained foreign bodies represents a challenge due to the proximity to vital neurovascular structures. 3,4 Preoperative CT scan is the preferred modality to show bony landmarks and vascular structures; however, although both CT scan and magnetic resonance imaging are increasingly being used, in the case of nail gun injuries significant artefacts secondary to the nail probably preclude these studies. 5 Blind removal of foreign bodies has been reported, 6 however the development of combined-multiportal endoscopic approaches enabled surgeons to reach different regions through minimally invasive routes with lower incidence of complications, lower morbidity, and mortality rates compared with traditional external approaches.…”
Section: Discussionmentioning
confidence: 99%
“…5 Blind removal of foreign bodies has been reported, 6 however the development of combined-multiportal endoscopic approaches enabled surgeons to reach different regions through minimally invasive routes with lower incidence of complications, lower morbidity, and mortality rates compared with traditional external approaches. 4,[7][8][9] Reconstruction of anterior skull base defects remains the most challenging issue in this field with postoperative cerebrospinal fluid leak, 9 however, the introduction of different vascularized nasoseptal flaps dramatically decreased the rates of postoperative cerebrospinal fluid leak and improved the quality of life of patients, reducing postoperative nasal crusting and hospitalization time rates ranging from 3.3% to 4.3%. [10][11][12] …”
Section: Discussionmentioning
confidence: 99%
“…The workup of pterygopalatine fossa lesions generally consists of nasal endoscopy, CT scan, and contrast‐enhanced MRI. Biopsy is indicated to rule out malignancy except in the case of suspected juvenile nasopharyngeal angiofibroma, and the decision to radically resect can be made based on tumor histology . PEComas typically exhibit benign behavior although they have been reported to metastasize, most commonly to cutaneous sites, although Tynski et al reported a case of PEComa metastasis to the orbit .…”
Section: Discussionmentioning
confidence: 99%
“…15 Given the anatomic relationship of the maxillary sinus with the nose, paranasal sinuses, and skull base, the TEPM is also performed during selected expanded endoscopic endonasal approaches in order to reach deeper regions, such as pterygopalatine fossa, infratemporal fossa, upper parapharyngeal space, lateral recess of the sphenoid sinus, Meckel's cave, and nasopharynx (the transantral or transmaxillary corridor). 8,9,[16][17][18] …”
Section: Indicationsmentioning
confidence: 99%
“…A middle meatal antrostomy with removal of the inferior portion of the uncinate process is performed. When the TEPM type 1 is harvested as a corridor to address adjacent anatomic areas, such as the intraorbital compartment, 19 the pterygopalatine fossa, 8 the lateral recess of the sphenoid, or the Meckel's cave, 16 the superior and/or posterior maxillary wall(s) can be partially drilled out, generally as far as the sagittal plane passing through the infraorbital nerve. The limits of resection are the posterior wall of the maxillary sinus, posteriorly; the inferomedial angle of the orbit, superiorly; the inferior turbinate, inferiorly; and the nasolacrimal duct, anteriorly ( Figure 1B).…”
Section: Surgical Techniquementioning
confidence: 99%